- #1

- 48

- 0

Then the proof goes on to consider coefficient of x viz a1=boc1 + b1co, and we know that a1=0modp and b1co=0modp so boc1=0modp...

...2 questions why is b1co necessarily =0modp ? and secondly why does it follow that boc1=0modp? ...

... i mean sure we know the sum b1co + boc1 =0modp but surely this doesn't imply b1co=0modp e.g 9=0mod3 but 9=5+4 and it is not true 5=0mod3

...2 questions why is b1co necessarily =0modp ? and secondly why does it follow that boc1=0modp? ...

... i mean sure we know the sum b1co + boc1 =0modp but surely this doesn't imply b1co=0modp e.g 9=0mod3 but 9=5+4 and it is not true 5=0mod3

Last edited: